(untitled) (SAARC Journal of Agriculture, 2014)
The experiment was conducted under plastic tunnel at Groundnut Research Station, Attock, Pakistan during 2006-2007 to 2008-2009 to determine water consumption by three off-season vegetables irrigated through drip and furrow systems, and to evaluate the comparative water use efficiency (WUE) of two irrigation systems in rain fed areas. Drip and furrow irrigation systems were tested on tomato, cucumber and bell pepper in this study. A permanent tunnel of 24 x 8 x 3 m was erected. Each crop was planted on 6 x 8 m under drip irrigation and on 6 x 2.70 m under furrow irrigation system. Water use efficiency was calculated as the ratio of total yield (kg) to total water consumed by the crop (m3). Each crop consumed less water under drip irrigation as compared to furrow irrigation system. Amomg crops, cucumber comsumed the least amount of water irrespective of irrigation systems. Average water use efficiency increased by 250% for tomato, 274% for cucumber and 245% for bell pepper under drip irrigation system as compared to furrow system. On the contrary, the average fruit yield increased only by 2.05% for tomato, 3.32% for cucumber and 2.35% for bell pepper in furrow irrigation over drip irrigation. This suggested that drip irrigation has a greater scope for production of off-season vegetables especially in water scarce areas of Pakistan. DOI: http://dx.doi.org/10.3329/sja.v12i1.21113 SAARC J. Agri., 12(1): 62-71 (2014)